Best Practices in Energy and Climate Change in the Universi-ty of Alcalá - Sarabia, María; Ocaña, Manuel (Journal of Sustainability Perspectives, 2023)
Since 2013, University of Alcalá has been taking part in the ranking of UI GreenMetric, as part of its sustainability policy. This ranking shows the effort of this University in promoting the sustainability in its three campuses and the surroundings, including the involving of all stakeholders from Rector to students. University of Alcalá has been always into the first places of Spain ranking due to the strong compromise that has been reflected in the policy of Rector’s managing and the strategic plan that covers actions to the 2037 represented as objectives, actions, and indicators of these actions.